2018
DOI: 10.1016/j.ijmultiphaseflow.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Statistical characterization of interfacial waves in turbulent stratified gas-liquid pipe flows

Abstract: This study presents a statistical analysis of interfacial waves in a turbulent stratified air-water flow inside a 10 cm diameter pipe. Wave elevation measurements were acquired using conductance probes with high sampling rate, Sr = 500Hz. Local wave parameters (elevation, crest height, trough height, etc.) were extracted using a zero-crossing technique. The evolution of their corresponding statistical distributions and statistical moments was investigated for varying flow conditions.The main goal of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
(66 reference statements)
2
5
0
1
Order By: Relevance
“…This indicates that in case B1, the waves have some degree of non-linearity. This is in line with the characterization of the wave field by Ayati & Carneiro (2018), where it is found that the U sg = 1.50 m/s case behaves according to Gaussian statistics, while the U sg = 2.1 m/s case deviates significantly from linear theory. Furthermore, the second quadrant of case B1 is considerably shorter and steeper than the other quadrants.…”
Section: Experimental Casessupporting
confidence: 89%
See 3 more Smart Citations
“…This indicates that in case B1, the waves have some degree of non-linearity. This is in line with the characterization of the wave field by Ayati & Carneiro (2018), where it is found that the U sg = 1.50 m/s case behaves according to Gaussian statistics, while the U sg = 2.1 m/s case deviates significantly from linear theory. Furthermore, the second quadrant of case B1 is considerably shorter and steeper than the other quadrants.…”
Section: Experimental Casessupporting
confidence: 89%
“…Meanwhile, case B belongs to a regime in which wave amplitudes remain more or less constant within a wide range of gas velocities above U sg = 1.75 m/s. In this regime, the waves are steeper and their statistical distributions deviate strongly from Gaussian statistics, implying the presence of nonlinear processes (Ayati & Carneiro, 2018). Similar results have been reported by Toffoli et al (2017) for a circular, fetch-unlimited wind-wave tank.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…The severity of breaking was however not reported, nor was the point of breaking onset in the flow map specified. Ayati and Carneiro 33 analyzed the statistics from interfacial wave probes in two-phase stratified flow, considering the same experimental setup and flow rate combinations closely matching the cases under investigation in the present work. By comparing the wave statistics with Gaussian statistics (linear wave theory), they observed a clear transition from a quasi-linear regime to a non-linear regime where linear wave theory considerably over predicts the maximum observed surface elevation η.…”
Section: Introductionmentioning
confidence: 95%